Evaluating Optimal Relationships for Estimating Suspended Sediment Discharge in the Balaroud River - Babak Lashkar-Ara; Farmehr Kiani (علوم و مهندسی آبیاری)
The transport of sediment in rivers is a crucial aspect of hydraulic engineering and environmental management. This study focuses on suspended sediment transport in the Balaroud River, a significant tributary of the Dez River in northern Khuzestan Province, Iran. We evaluated various sediment transport equations, including those by Rouse (1937), Lane & Kalinske (1941), Brooks (1958), Bagnold (1966), and Yang (1996), to determine the most accurate model for estimating suspended sediment load in this river. Data spanning from 2007 to 2020, collected from the Khuzestan Water and Power Authority (KWPA), were analyzed to compare these models against measured sediment loads. The Rouse method proved to be the most reliable, achieving approximately 80% accuracy in estimating suspended sediment load. The modified Yang equation followed with about 60% accuracy, while accuracy for Brooks' method was around 49%. Conversely, the Bagnold (1966) and Lane & Kalinske (1941) models demonstrated significantly lower accuracies of 21% and 12%, respectively. The study reveals that Rouse and Yang equations align better with the Balaroud River's conditions, marked by its sandy substrate and the influence of the Balaroud dam on flow dynamics. The findings underscore critical discrepancies among the evaluated equations and the necessity for case-specific assessments to enhance sediment transport predictions. This research highlights the importance of selecting models tailored to the unique characteristics of each river system for effective sediment management and environmental conservation. Recommendations include prioritizing the Rouse equation for similar rivers and pursuing further research to develop models suited to diverse sediment transport dynamics.